Human geography as social science: retrospect and prospect - Buttimer, Anne (ERDKUNDE, 2003)
Major re-orientations in practices of human geography during the second half of the twentieth century are outlined here in terms of four distinct stances assumed by scholars vis-à-vis their objects of study: (1) observation, the stance assumed by most geographers from the origins of this field as academic discipline to the 1950's, (2) participation, starting in the 1960s and reflecting an eagerness to demonstrate the relevance of geographical analyses for the elucidation and/or solution of social issues, (3) interpretation, from the mid-1970's on, reflecting an awareness of reflexivity and the need for dialogue, and (4) representation, inspired by modernist vs post-modernist tensions from the late 1980s on. At the dawn of a new millennium, the paper argues, the harvest of the previous decades yields contradictory evidence. Increasing levels of functional specialisation in science throughout the 20c have led to problems of scholarly communication, mutual understanding and knowledge integration. Might recent advances in information technology mitigate or re-inforce these problems? The institutional separation of physical and human geography has also substantially weakened the discipline's capacity to comprehensively address environmental issues. And despite rapid rise in interdisciplinary global research programmes during the late twentieth century, too, environmental problems persist. Finally, while most major issues of geographical concern today transcend territorial boundaries, conventional practices of geography remain tightly shaped by national institutions. There is an emerging consensus, however, about one conclusion, i.e., that there are many geographies, and multiple geographical knowledges, each embedded in and serving the interests of particular social contexts. A worthwhile goal today would be to promote dialogue among the diverse geographical knowledges and to assess their implications for humanity's modes of dwelling.